2021
DOI: 10.1021/acs.biochem.1c00183
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of d-glycero-l-gluco-Heptose in the Capsular Polysaccharides of Campylobacter jejuni

Abstract: Campylobacter jejuni is the leading cause of food poisoning in the United States and Europe. The exterior cell surface of C. jejuni is coated with a capsular polysaccharide (CPS) that is essential for the maintenance and integrity of the bacterial cell wall and evasion of the host immune response. The identity and sequences of the monosaccharide components of the CPS are quite variable and dependent on the specific strain of C. jejuni. It is currently thought that the immediate precursor for the multiple varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(38 citation statements)
references
References 29 publications
0
38
0
Order By: Relevance
“…The wild-type epimerases from the HS:2, HS:3, HS:10, HS:15, HS:23/36, HS:41, and HS:42 serotypes, in addition to the variants made from the HS:3 and HS:15 serotypes, were purified according to the procedure reported previously. 15 Similarly, the wild-type C4-reductases from serotypes HS:2, HS:3, and HS:15 were expressed and purified according to a published procedure. 15 E. coli BL21(DE3) competent cells were transformed by the appropriate plasmids.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The wild-type epimerases from the HS:2, HS:3, HS:10, HS:15, HS:23/36, HS:41, and HS:42 serotypes, in addition to the variants made from the HS:3 and HS:15 serotypes, were purified according to the procedure reported previously. 15 Similarly, the wild-type C4-reductases from serotypes HS:2, HS:3, and HS:15 were expressed and purified according to a published procedure. 15 E. coli BL21(DE3) competent cells were transformed by the appropriate plasmids.…”
Section: ■ Introductionmentioning
confidence: 99%
“…6 D ). These amino acids are well conserved among orthologs, and H64/Y134 are the catalytic base and acid proposed from previous studies ( 41 , 42 , 43 , 44 ). The conformation of these side chains is very similar to that seen in complexes of other enzymes with substrate analogs ( Fig.…”
Section: Resultsmentioning
confidence: 74%
“…RmlC is part of a family of epimerases that use a deprotonation/reprotonation mechanism ( 40 ). RmlC uses a histidine base to deprotonate the substrate and a tyrosine acid to reprotonate from the opposite side of the sugar ( 41 , 42 , 43 , 44 ). The same residues are likely involved in epimerizing at both 3’’ and 5’’ positions: the sugar ring flips between the two reactions to present the second site to be epimerized to the catalytic base and acid ( 41 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…jejuni NCTC 11168 is composed of 35 genes, as illustrated in Figure S1 . Previous investigations have functionally characterized the genes necessary for the biosynthesis of the d -glycero- l -gluco-heptose moiety and modification (Cj1152, Cj1423, Cj1424, Cj1425, Cj1427, Cj1428, and Cj1430). In addition, the enzymes Cj1415, Cj1416, Cj1417, and Cj1418 have been shown to be required for the biosynthesis of the phosphoramidate modification, and gene knockout experiments have identified the enzymes (Cj1422 and Cj1421) required for the transfer of the phosphoramidate modifications to specific sugar receptors. , More recently, we have shown that Cj1441 is required for the conversion of uridine diphosphate (UDP)-glucose to UDP-glucuronate and that this enzyme is unable to catalyze the formation of an amide bond via the attack of an amine substrate with the putative thioester intermediate formed during the oxidation of UDP-glucose . The enzymes required for the biosynthesis of the two amines (serinol and ethanolamine) found in the HS:2 capsule are currently unknown.…”
Section: Introductionmentioning
confidence: 99%